Implementasi Teknologi Augmented Reality (AR) terhadap Peningkatan Pengalaman Pengguna di Dinas Perpustakaan dan Kearsipan Kota Solok - Narti, Dika Mai; Desriyeni, Desriyeni (Lembaga Yasin AlSys, 2025)
The rapid advancement of information technology compels libraries to continuously innovate in enhancing service quality for users. One such innovation currently being implemented is Augmented Reality (AR), which is believed to enrich interactivity and improve user experience in accessing information. This study aims to describe how the implementation of AR can enhance user experience, particularly in terms of engagement, convenience, and satisfaction. A descriptive quantitative method was employed, with data collected through questionnaires distributed to 150 users of AR technology at the Solok City Library and Archives Office. The data were analyzed based on two main variables AR technology and user experience using indicators such as AR quality, system usability, user engagement, and comfort. The results show that all indicators received average scores above 3.69 on a 4-point scale, reflecting a very positive perception of the AR system. AR quality received the highest score, averaging 3.71, indicating that the technology is easy to use and provides relevant information. Thus, the implementation of AR is proven effective in enhancing interaction quality, user comfort, and information-seeking efficiency in the library, offering a more adaptive and engaging user experience.